TRANSFORMASI POTENSI PEMUDA DALAM MENDUKUNG TATA KELOLA DESA PARTISIPATIF DI KABANJAHE KABUPATEN KARO - Walid Musthafa Sembiring; Fuad Putera Perdana Ginting; Miftahul Husna Siregar; Bimby Hidayat; Taufik Abdullah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to analyze the role of youth in supporting participatory village governance in Kabanjahe Subdistrict, Karo Regency. The method used is a qualitative approach with case study techniques. Data collection was carried out using in-depth interviews and documentation studies. The data was analyzed interactively through the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that youth have a significant role. Specifically, youth in village governance can be agents of innovative change, as social control and village development, such as involvement in Musrenbangdes and economic development. However, this role is constrained by village cultural norms, village institutions, and limited formal participation spaces. The study concludes that there is a need for collective awareness of the potential of youth, the importance of institutionalizing youth participation in village government policy-making, and the need for an ecosystem that includes collaborative and affirmative approaches to the role of youth.